Fostering spiritual resilience and vitality in formerly incarcerated persons of African American descent - Banfield, Lori E. (Journal of pastoral care & counseling, 2019)
The process of reentry for formerly incarcerated persons can be a burdensome, stigma-laden transition, and any difficult transition requires resilience. African Americans—the group most impacted by incarceration trauma—commonly depend on faith leaders in times of crisis to provide meaning, encouragement, and guidance, fostering spiritual resilience. This study conceptualizes spiritual resilience and proposes it as a vital quality for successful reentry; giving credence to the significant role clergy and pastoral clinicians play in mediating restorative reintegration.